Effect of Using Continuous Care Model on Sleep Quality of Chemical Warfare Victims with Bronchiolitis Obliterans - S Mehdizadeh; MM Salaree; A Ebadi; J Aslani; Z Naderi; N Jafari Varjoshani (Tehran University of Medical Sciences, 2010)
Background & Objective: Poor physical and psychological health status in chemical warfare victims could result in decreasing quality of sleep. This study was conducted in order to evaluate the effect of using Continuous Care Model on sleep quality in chemical warfare victims with bronchiolitis obliterans. Methods & Materials: A total of 62 chemical warfare victims with bronchiolitis obliterans were recruited to the study. The participants were randomly allocated to experimental and control groups. The Continuous Care Model was used to experimental group for a period of two months. The quality of sleep was measured using Pittsburgh Sleep Quality Index (PSQI) before and after the intervention in both study groups. Data were analyzed using independent sample t-test, and paired t-test in the SPSS-version 15. Results: There were significant differences between experimental and control groups in the means of Subjective Sleep Quality, Sleep Disturbances, Use of Medications, and global scores after the intervention (P<0.05). Conclusion: Using Continuous Care Model had positive effect on sleep quality in chemical warfare victims suffering from bronchiolitis obliterans.